Peningkatan Kepedulian Konsumen Terhadap Produk Ramah Lingkungan Menggunakan Green Brand Image Menghasilkan Green Brand Love - Rasidin, Berliana; Yolanda Masnita (Cv. Syntax Corporation Indonesia, 2023)
Green brands are companies that implement sustainable business and preserve the environment. Environmental problems have a negative impact on every living thing, the existence of environmental problems creates companies to carry out green marketing strategies to meet the consumer market that is starting to be aware of the environment. The purpose of this study was to analyze the effect of green brand image, green brand trust, and customer satisfaction on green brand love. Respondents of this study were users of The Body Shop, Mustika Ratu, or Wardah brand cosmetics. This research instrument is a questionnaire assisted by Google Forms. This type of research data is primary data, to test the hypothesis using structural equation modeling (SEM) analysis. The results in this study are that there is a positive and significant effect of green brand image on green brand trust, there is a positive and significant effect of green brand image on customer satisfaction, there is no positive effect of green brand trust on green brand love, there is a positive effect of customer satisfaction on green brand love, there is a positive and significant effect of green brand image on green brand love.